Towards combining the triple helix concept with competence-based approach of educational management theory. (6th March 2019) - Gamidullaeva, Leyla A.; Vasin, Sergey M.; Surovitskaya, Galina V.
The purpose of this study is to find ways of combining the concept of the triple helix of university-industry-government relationships with competence-based approach of university management theory. The methodological framework is based on a number of theoretical provisions, which integration allowed to substantiate the concept of improving mechanisms of master students' research competencies formation in universities. Correlation analysis with the use of datasets characterising the effectiveness of the mechanisms of research competencies formation was carried out. The approach to improving master students' research competencies, presented in this research, is in line with the world and national trends of development in higher education sphere, which creates assumptions for the shift to the new quality of training competitive staff for regional innovation systems. The obtained research results are of interest to the regional development authorities, because they may be incorporated into management practices to improve the efficiency and competitiveness of regional innovation systems.